Exacerbation of Asthma during Pregnancy: Fetomaternal Outcomes - Ghimire, Ram Hari; Pokhrel Ghimire, Sita; Ghimire, Ashima (Journal of Nobel Medical College, 2016)
Background Asthma is a common occurrence during pregnancy. Exacerbation during pregnancy represents a important and challenging medical problem and may result in poor fetomaternal outcomes. Until now, there are no studies comparing the fetomaternal outcomes in pregnant women with case (asthma) exacerbation and with control group (non-asthma) women of similar age and period of gestation. Therefore, we analysed selected fetomaternal outcomes retrospectively in these group of women.Material & Methods This is a retrospective observational comparative study. During the study period, total number of deliveries was 5,568. Women who were admitted with the diagnosis of exacerbation of asthma during pregnancy between 1st Jan 2015 to 31st Dec were included in the study. These cases were compared with random selection of controls who were admitted in the same duration of time for the delivery without asthma after matching maternal age and period of gestation. Ethical clearance was obtained before the study. Fetomaternal outcomes were compared between women with exacerbation of asthma and non-asthma.Results One hundred and eight pregnant women from each asthmatic and non- asthmatic group were analysed for selected fetomaternal outcomes. The mean age of asthmatic and nonasthmatic group was 23.2± 4.3 and 24.9±3.2 years respectively. LSCS, UTI and preeclampsia were more common in asthmatic women. Birth weight and APGAR score was lower in babies with asthmatic women. Inpatient care and mortality rate were more common in babies of asthmatic women.Conclusion Exacerbation of asthma during pregnancy may result in poor fetomaternal outcome. Therefore, a more careful monitoring of women with exacerbation of asthma during pregnancy and delivery is required.Journal of Nobel Medical College Vol.5(2) 2016; 32-36